Yearbook of physical anthropology : supplement 3 to the American Journal of Physical Anthropology - American Association of Physical Anthropologists; Malina, Robert M. (New York : Alan R. Liss, Inc., 1982)
"The Yearbook of Physical Anthropology is an American Association of Physical Anthropologists' publication, published once per year as a supplement to the American Journal of Physical Anthropology. "
Advances In selected areas of human work physiology yearbook phys. anthropol. Bouchard, Claude, Thibault, Marie-Christine, and Jobin, Jean
Includes bibliographical references and index.
in English.
Keywords: Physical anthropology -- Periodicals. Societies. Serials; Antiquities, Prehistoric; Prehistoric peoples